Death: One’s Ownmost Possibility (Freedom) or a Social Event? An Exploration of the Works of Martin Heidegger and Emmanuel Levinas - Anthony Kwaku Boakye (E-Journal of Humanities, Arts and Social Sciences)
This study explored the works of Martin Heidegger and Emmanuel Levinas and how they both approached the subject of death, as to whether death should be understood in the context of one’s ownmost possibility or just a social event. This paper examined the notion of death as construed by both Levinas and Heidegger and how it might help to understand the nature of the world, especially the question of how one dies. The methodology used in this study is qualitative. The understanding of death according to Heidegger has been grounded in his concept of Dasein the basic fact of our existence. Due to this, Dasein must live an authentic life through the recognition of mortality. Levinas strongly argues that to be responsible for the Other is deep-rooted in one’s subjective makeup. Hence, to meet the Face of the Other is to have the notion of meeting a Being in eternity. This is when one philosophizes beyond oneself by going beyond the limits of what the mind can tell. That goes beyond what Edmund Husserl and Heidegger emphasized, the phenomenon of being (the being of subjects and objects). In a sense, one goes beyond history and consciousness where even in death it is not only the I that dies but also the Other. This means death now becomes a relational activity. The death of the Other is the death of the entire community. This study will contribute to the scholarly understanding that one dies alone.